2022
DOI: 10.1108/sr-11-2021-0447
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and performance of CNTs-Pt formaldehyde sensor and CNTs-Au glucose sensor

Abstract: Purpose Since carbon nanotubes (CNTs) were discovered by Iijima in 1991, they have gained more and more attention by people because of their unique physical and chemical properties. The CNTs have one-dimensional nanostructure, high surface adsorption capacity, good conductivity and electronic ballistic transmission characteristics and therefore have excellent mechanical, electrical, physical and chemical properties. CNTs are ideal basic materials to make nanometer gas sensors. Nanometallic materials function a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Since CNTs were discovered by Iijima in 1991, they have received attention continuously because of their unique physical and chemical properties. (100) Ye et al were pioneers in applying CNTs in enzyme-free glucose sensors and found that CNTs improved the sensitivity of the electrodes to glucose detection. (101) Baghayeri et al prepared Ag NPs on metformin-functionalized MWCNTs using an electrochemical method.…”
Section: Carbon-based Enzyme-free Glucose Sensorsmentioning
confidence: 99%
“…Since CNTs were discovered by Iijima in 1991, they have received attention continuously because of their unique physical and chemical properties. (100) Ye et al were pioneers in applying CNTs in enzyme-free glucose sensors and found that CNTs improved the sensitivity of the electrodes to glucose detection. (101) Baghayeri et al prepared Ag NPs on metformin-functionalized MWCNTs using an electrochemical method.…”
Section: Carbon-based Enzyme-free Glucose Sensorsmentioning
confidence: 99%
“…8,9 Composites that incorporate graphene, conductive polymers, and metal nanoparticles offer improved performance and expand the range of applications for these materials. Graphene/conductive polymer/metal nanoparticle composites can detect a variety of compounds and molecules such as glucose, urea, protein, and DNA, [10][11][12][13][14] indicating promising prospects in the eld of biosensing.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies are being carried out using nanomaterial supports to adsorb formaldehyde. Carbon nanomaterials such as carbon nanotubes [ 10 , 11 , 12 ] and graphene [ 13 , 14 , 15 ] have been recently employed in various attempts to adsorb formaldehyde. Zeolite [ 16 , 17 , 18 ], active carbon [ 19 , 20 ], and porous silica nanomaterials [ 21 , 22 , 23 ] are also utilized as support materials for adsorption.…”
Section: Introductionmentioning
confidence: 99%